A renewable heat-treatment-free integrated die-casting aluminum alloy and a preparation method thereof

By introducing BCC phase and specific refining agents into aluminum alloys, combined with spraying and degassing technology, the problems of aluminum alloy heat treatment deformation and high hydrogen content are solved, and high strength and low hydrogen content are achieved, and aluminum alloy materials are improved. Mechanical properties and production efficiency of alloys.

CN118703847BActive Publication Date: 2024-12-17SHANDONG HAIHUA GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411199924.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-17
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Existing aluminum alloy materials are prone to deform and produce bubbles during heat treatment, resulting in high waste rate and high hydrogen content affects mechanical properties and corrosion resistance. The existing hydrogen removal technology is difficult to effectively reduce the hydrogen content to below 0.1ml/100g Al. , leading to hydrogen embrittlement problems.

Method used

Renewable heat-free integrated die-cast aluminum alloy with BCC phase is adopted, and the alloying elements and process flow are preferred, including the use of Nb-35Ti-15Al-10Mo alloy as a refining agent and MgCl2, KCl, CaF2, BaCl2, etc. , combined with nitrogen blowing and rotary degasser, the aluminum liquid treatment with low hydrogen and low slag is achieved, and a high-strength aluminum alloy with matrix α-Al solid solution, Mg2Si and BCC phase is formed.

Benefits of technology

The high yield strength, tensile strength and elongation of aluminum alloy are achieved, which significantly reduces hydrogen content and slag content, avoids hydrogen embrittlement problems, and improves the full life cycle performance and production efficiency of aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118703847B_ABST
    Figure CN118703847B_ABST
Patent Text Reader

Abstract

The present invention discloses a renewable heat-treatment-free integrated die-cast aluminum alloy and a preparation method thereof, belonging to the technical field of aluminum alloy materials. The weight percentage of each component in the die-cast aluminum alloy is Mg: 5.0-8.0%, Si: 2.0-3.8%, Mn: 1.0-1.5%, Zn: 0.1-0.5%, Be: 0.003-0.005%, Nb: 0.02-0.08%, Ti: 0.0175-0.07%, Mo: 0.005-0.02%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al. The die-cast aluminum alloy phase includes a matrix α-Al solid solution, Mg 2 Si and BCC phase, BCC phase is evenly distributed in the grain boundary area of ​​die-cast aluminum alloy, the high melting point BCC phase has a hydrogen adsorption capacity of >150ml / g in the temperature range of 20-700℃, and it does not melt when heated to 1980℃ and kept for 2h, the hydrogen content of aluminum liquid is ≤0.05ml / 100g Al, and the slag content is ≤0.01mm 2 / kg, the obtained heat-treatment-free integrated die-casting aluminum alloy has high resistance to hydrogen embrittlement and excellent strength and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to a renewable heat treatment-free integrated die-casting aluminum alloy and a preparation method thereof. Background Art

[0002] In September 2020, Tesla officially announced that Model Y adopts an one-piece die-cast rear floor assembly, reducing the number of parts from 70 to 1~2, the total weight of the rear floor by 30%, and the manufacturing cost of the whole vehicle by 40%. It only takes 18-24 months to develop a new car, while the development cycle of competitors in the same period takes about 3-4 years. The current plan of the Austin factory in Texas can reduce the number of front and rear floor components from 171 to 2, and the number of welding points can be reduced by more than 1,600. In April 2023, the Ministry of Industry and Information Technology and three other departments jointly issued the "Guiding Opinions on Promoting the High-Quality Development of the Forging and Pressing Industries", proposing to fully realize the industrial application of advanced process technologies such as integrated die-casting by 2025. Domestic leading new forces will follow up in an all-round way to accelerate the realization of integrated die-casting from "1" to "N". Among them, models such as NIO ES7 / ET5 / ES6, HiPhi Y, Zeekr 009, Xiaopeng G6, and M9 have all been mass-produced. Traditional old independent brands such as Great Wall, Changan, FAW, Geely, Dongfeng, etc. are also increasing their investment in integrated die-casting technology, and internationally renowned car companies such as Ford, Volkswagen, Mercedes-Benz, Volvo, etc. are also actively developing and promoting integrated die-casting structural parts. Integrated die-casting technology demonstrates the typical characteristics of new quality productivity.

[0003] Traditional aluminum alloys must be heat treated (solid solution-quenching-aging) before use. Integrated die-casting technology integrates dozens or even hundreds of single parts into a large or super-large structural part. Some parts are thin and some are thick. The thin parts are only 2mm or 3mm thick and cannot be heat treated. Otherwise, they will be severely deformed and produce bubbles and have to be scrapped. The development of heat-treatment-free die-casting aluminum alloy materials is the key to integrated die-casting technology. my country's heat-treatment-free integrated die-casting aluminum alloy material industry started late, and many foreign aluminum alloy brands such as Castasil37 of Rheinland, Aural6 of Magna, C611 of Alcoa and Tesla Alloys of Tesla were used for secondary development. The independent research and development and innovation capabilities are insufficient, and there is a lack of in-depth thinking on the technical connotation of heat-treatment-free aluminum alloy materials. There is even a false rumor due to unclear technical principles. Take Alcoa's C611 aluminum alloy as an example. This alloy is not strictly a heat-treatment-free integrated die-casting aluminum alloy material. Because C611 contains a certain amount of Mg, T5 heat treatment or T85 coating and baking treatment of the alloy casting can further improve the yield strength. The specific heat treatment process is the core technology of C611 alloy. Hydrogen is the only gas that can dissolve in large quantities in molten aluminum. According to measurements, hydrogen accounts for more than 85% of the gas present in aluminum alloys, so the "gas content" of aluminum alloys can be regarded as "hydrogen content". Hydrogen is very harmful to the performance of aluminum and aluminum alloys. It is very easy to precipitate from the castings during the heat treatment process to form surface bubbles. The scrap rate caused by excessive hydrogen content accounts for about half of all aluminum casting scraps. Aluminum castings are very prone to defects such as pinholes and pores, which greatly reduce the mechanical properties and internal quality of the castings. The main reason for the pinholes in aluminum castings is the dissolution and precipitation of hydrogen in aluminum and its alloys. Hydrogen not only causes macroscopic defects in aluminum, but also affects the organizational structure, and has an impact on a series of properties such as strength, fatigue, toughness, corrosion resistance, and anodizing. Although heat-treatment-free aluminum alloys avoid the deformation of die-castings and the generation of surface bubbles caused by heat treatment, if the hydrogen content in the aluminum alloy is too high, in addition to reducing the strength and toughness of aluminum alloy die-castings, it will significantly reduce fatigue life and cause hydrogen embrittlement under the induction of external environments such as alternating stress, impact loads, and rain and seawater. The hydrogen content required for hydrogen embrittlement in aluminum and aluminum alloys is only about 0.1ml / 100g Al, which is one to two orders of magnitude lower than the hydrogen content in steel and titanium alloys. Therefore, for the entire life cycle of heat-treatment-free aluminum alloy die-castings from melting and casting, loading and application to scrapping, the hydrogen content of the aluminum liquid must be controlled below 0.1ml / 100g Al from the melting and casting stage of the aluminum alloy to avoid extreme accidents such as brittle fracture caused by hydrogen embrittlement.Since the 1990s, domestic aluminum liquid purification technology has been greatly improved, and the hydrogen content can reach the level of 0.12~0.15ml / 100g Al, but it still lags behind the international advanced level as a whole. For example, Alcoa469 method can control the hydrogen content in aluminum liquid at 0.08~0.15ml / 100g Al, and the rotating nozzle inert gas flotation method (SNIF) developed by Union Carbide Corporation can control the hydrogen content in aluminum liquid at 0.08~0.12ml / 100g Al. There are two types of methods for removing hydrogen from aluminum alloys: one is to "drive" hydrogen out of the aluminum liquid based on the principle of bubble floating, and the other is to "anchor" hydrogen inside the aluminum liquid. In practice, it is difficult to stabilize the hydrogen content of aluminum liquid below 0.1 ml / 100 g Al by the external driving method based on the principle of bubble floating. The Chinese patent document with publication number CN116103543 A discloses a regenerated high thermal conductivity die-casting aluminum alloy containing rare earth elements and a preparation method thereof. The rare earth elements La and Ce with a purifying effect on aluminum alloy are added. The elements La and Ce combine with hydrogen (H) in the aluminum liquid to reduce the hydrogen content in the aluminum liquid. The Chinese patent document with publication number CN115109961 A discloses an aluminum alloy rare earth refining agent and a preparation method thereof. The rare earth element reacts with [H] at high temperature to generate a stable rare earth hydride, thereby removing H2 from the aluminum liquid to achieve the purpose of removing [H]. In addition, the Chinese patent document with publication number CN109652686 A large number of patent documents such as CN115874093 B, CN105624448 B, etc. use rare earth elements and hydrogen in aluminum liquid to generate rare earth hydrides to achieve the purpose of fixing and removing hydrogen. The technical principle of "anchoring" hydrogen was first seen in the article "Interaction between mixed rare earths and hydrogen in cast aluminum alloys and its influence on performance" published in the journal "Foundry" in 1985. The article mentioned that "after rare earth metals are added to aluminum liquid, when they meet hydrogen atoms in aluminum liquid, they can quickly form stable hydrides such as CeH2, LaH2, and YH2. These hydrides are stable at normal temperature of aluminum liquid, and they do not decompose into hydrogen during solidification and cooling, nor do they gather into bubbles. Therefore, the dehydrogenation effect of rare earth in aluminum liquid is to fix free hydrogen atoms in compounds, thereby reducing the concentration of hydrogen." However, high-performance aluminum foam is prepared by utilizing the instability of rare earth metal hydrides, that is, the principle of hydrogen release from rare earth metal hydrides. In fact, rare earth metals react slowly with hydrogen at room temperature, and react quickly with hydrogen when heated to 200°C. As the temperature rises, the rare earth metals are hydrogenated, and the generated hydrides also begin to decompose into hydrogen and rare earth metals. When the temperature reaches 600-800°C, they tend to be in equilibrium (see Northeastern University doctoral dissertation "Study on the Preparation of Aluminum Foam by Hydrogenation of Rare Earth and Zirconium Hydride" page 24). Figure 2 .5. Master's thesis of Xi'an University of Technology, "Preparation and properties of hydrogenated mixed rare earth foaming agent and corresponding aluminum foam" 32 pages Figure 4-4 ), La and Ce rare earth hydrides decompose fastest at 696~760℃. Unstable rare earth hydrides release hydrogen, which will increase the hydrogen content of molten aluminum, especially as the temperature of molten aluminum drops to the liquidus-solidus temperature. Due to the solubility difference of hydrogen in liquid aluminum and solid aluminum of up to 20:1, a large amount of hydrogen will escape from the molten aluminum at this time. In addition, the pouring process will absorb hydrogen, which will greatly increase the hydrogen content of the aluminum ingot and easily cause loose defects in the casting, which not only reduces the air tightness and corrosion resistance of the casting, but also significantly reduces the mechanical properties of the alloy, and even increases the pinhole degree, causing the casting to fail to meet the first-level pinhole degree requirements and be scrapped. In addition, considering the whole life cycle of the casting, under the induction of application scenarios such as high temperature and high humidity water vapor, alternating impact stress, etc., the hydrogen in the external environment and the supersaturated hydrogen atoms retained in the solid aluminum will be "restless". Once the hydrogen atoms combine into hydrogen molecules, they will be accompanied by a sharp volume expansion, and the internal stress generated can reach 10 4 MPa, which is enough to "tear" the aluminum alloy from the inside. In summary, heat-treatment-free aluminum alloys actually put forward more stringent requirements on aluminum alloy materials and each link of processing and preparation. Only by starting from the technical source of high-strength and tough aluminum alloy materials, developing aluminum alloy material formulas with unique chemical elements and original aluminum liquid treatment and material preparation process technologies, and at the same time realizing the use of recycled waste aluminum with complex components and more impurities as raw materials to manufacture high-strength and tough heat-treatment-free aluminum alloy materials, can we truly reduce costs and increase efficiency for enterprises, and promote the benign and healthy development of aluminum alloy material technology and heat-treatment-free integrated die-casting industry. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a renewable heat-treatment-free integrated die-cast aluminum alloy and a preparation method thereof from the perspective of the entire life cycle of the die-cast aluminum alloy. The renewable heat-treatment-free integrated die-cast aluminum alloy has extremely low hydrogen and slag content, high yield strength, tensile strength and elongation, and exhibits excellent toughness, while also being able to effectively overcome the hazards caused by hydrogen embrittlement.

[0005] To achieve the above purpose, the weight percentage of each component in the die-casting aluminum alloy is Mg: 5.0-8.0%, Si: 2.0-3.8%, Mn: 1.0-1.5%, Zn: 0.1-0.5%, Be: 0.003-0.005%, Nb: 0.02-0.08%, Ti: 0.0175-0.07%, Mo: 0.005-0.02%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al.

[0006] The die-cast aluminum alloy phases include matrix α-Al solid solution, Mg2Si and BCC phase (Body-centered cubic phase), the BCC phase is evenly distributed in the grain boundary region of the die-cast aluminum alloy, the BCC phase has a hydrogen adsorption capacity of more than 150 ml / g in the temperature range of 20 to 700° C., and does not melt when heated to 1980° C. and kept warm for 2 hours; the die-cast aluminum alloy has a die-cast tensile strength of 350 to 420 MPa, a yield strength of 180 to 240 MPa, and an elongation of 8 to 20%.

[0007] The preparation method of the present invention comprises the following steps:

[0008] 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 750-770°C, stir it evenly for 15-30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680-710°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0009] 2) The aluminum liquid is heated to 710-730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10-15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20-30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent spraying speed is 0.6-1.0 kg / min, and the nitrogen pressure is 0.35-0.8 MPa;

[0010] 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor rotation speed to 400-450r / min, argon pressure to 0.2-0.35MPa, argon flow rate to 10-15L / min, and degassing time to 10-15min; sprinkle a layer of slag remover on the surface of the degassed aluminum liquid for slag removal, let it stand for 10-20min, control the aluminum liquid temperature to 660-690℃, and after two-stage filtration, obtain a hydrogen content of ≤0.05ml / 100g Al and a slag content of ≤0.01mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor to produce a heat-treatment-free die-casting aluminum alloy ingot.

[0011] The refining agent in step 2) is composed of the following components in parts by weight:

[0012] MgCl2 30-55 parts;

[0013] KCl 30-50 parts;

[0014] CaF2 5-10 parts;

[0015] BaCl2 5-10 parts;

[0016] 3 to 6 parts of Nb-35Ti-15Al-10Mo alloy.

[0017] The Nb-35Ti-15Al-10Mo alloy in the refining agent is a powder particle with a particle size of 1-2 μm obtained by repeatedly smelting three times in a magnetic suspension smelting furnace and then ball milling and sieving. The refining agent is prepared by mixing the components according to the corresponding percentage and feeding them into a ball mill with a rotation speed of 100-500 r / min, mixing and grinding them into powder, and then passing through a 20-40 mesh sieve.

[0018] The slag remover in step 3) is MgCl2 and KCl in a weight ratio of 1: 1-1.5; the two-stage filtration is to set a foam ceramic filter with a thickness of 8-20 mm and a pore size of 20-80 at the outlet of the aluminum liquid in the insulation furnace for primary filtration, and then flow through an alumina gravel deep bed filter with a particle size of 2-10 mm for secondary filtration.

[0019] The present invention has the following beneficial effects:

[0020] Starting from the whole life cycle of heat-treatment-free integrated die-casting aluminum alloy, the present invention first creates a renewable heat-treatment-free integrated die-casting aluminum alloy with extremely low hydrogen and slag content and a preparation method thereof, and constructs a high-strength and toughness die-casting aluminum alloy composed of matrix α-Al solid solution, Mg2Si and BCC phase by optimizing and adjusting the types and contents of alloying elements; Mg is an important strengthening element of die-casting aluminum alloy, and Mg and Si can form Mg2Si strengthening phase to significantly enhance the strength of die-casting aluminum alloy. The higher the Mg content, the higher the strength of die-casting aluminum alloy. However, if the Mg content is too high, the plasticity of die-casting aluminum alloy will be reduced. In the actual production process, the atomic ratio of Mg / Si is about 1.73, which has good comprehensive mechanical properties; Si is the main alloying element of die-cast aluminum alloy. Si can improve the casting fluidity of aluminum alloy in die-cast aluminum alloy. At the same time, Si and Mg can form Mg2Si strengthening phase to significantly enhance the strength of die-cast aluminum alloy. The higher the Si content, the better the fluidity of die-cast aluminum alloy, and the higher the strength. A certain content of Si and Mn elements are conducive to demoulding and continuous operation of die casting, but too high Si content will reduce the plasticity of die-cast aluminum alloy; MnAl6 generated by the reaction of Mn element and matrix Al has a strong affinity with pure aluminum. The present invention has the same potential, which can effectively improve the corrosion resistance of aluminum alloy. At the same time, Mn, as a high-temperature strengthening phase, has the effect of increasing the recrystallization temperature and inhibiting the coarsening of recrystallized grains, and can achieve solid solution strengthening of the alloy. In addition, Mn can generate pelletized A13 (Fe, Mn) with Fe element, which effectively eliminates the harmful effect of Fe on aluminum alloy. Therefore, the present invention uses recycled aluminum with a high impurity iron content as raw material to achieve waste aluminum regeneration and reduce costs; Zn element has a high solid solubility in Al and has an obvious solid solution strengthening effect. At the same time, Zn can generate MgZnX multi-component strengthening phase with Mg, where X is Al, Si, and Mn. One or more MgZnX multi-component strengthening phases can weaken the diffusion capacity of Mg and improve the corrosion resistance of the material to a certain extent; a small amount of Be added to the aluminum liquid can form a layer of beryllium oxide film on the surface of the aluminum liquid, reduce slag, improve the purity of the aluminum liquid and improve fluidity. At the same time, because Be has a great affinity for oxygen and nitrogen, it has a high efficiency in deoxidizing and denitrifying. Ti, as a traditional aluminum alloy grain refining element, can refine the grains and improve the strength and toughness of the aluminum alloy by generating AlTi3 with Al. Mo, as a characteristic alloying element, can form AlMo3~Al in the alloy. 12 Mo

[0021] Thirteen kinds of metal compounds are dispersed in the matrix grain boundaries, which improve the room temperature and high temperature strength of the alloy. The melting point of Nb is 2468℃, and it has a strong hydrogen absorption capacity. The actual soluble H is 50% (atomic percentage) at 0.1MPa. The BCC phase Nb-35Ti-15Al-10Mo niobium-based alloy with the above-mentioned Ti, Mo and Nb element characteristics has a strong hydrogen absorption capacity and thermal stability. The hydrogen adsorption capacity is greater than 150ml / g in the temperature range of 20-700℃, and it does not melt when heated to 1980℃ and kept warm for 2h, ensuring extremely low hydrogen content throughout the entire process of aluminum liquid solidification and the entire life cycle of die-casting aluminum alloy, avoiding the occurrence of hydrogen embrittlement. In addition, high-hardness niobium-based alloy fine particles of 1-2μm are evenly distributed in the grain boundary area, acting as an effective nucleation substrate, refining the grain structure, reducing the degree of segregation, and promoting the refinement and homogenization of the matrix α-Al solid solution phase and Mg2Si phase.

[0022] The two-stage filtration of the foam ceramic filter + deep bed filter and the low-temperature insulation static sedimentation for a total time of 30 to 50 minutes effectively reduce the slag content and the iron content introduced by the recycled aluminum. Hydrogen content ≤ 0.05ml / 100g Al, slag content ≤ 0.01mm 2 / kg of high-purity aluminum liquid with low hydrogen and slag content and the combined effects of fine grain strengthening, solid solution strengthening and dispersion strengthening make the yield strength of the die-casting aluminum alloy of the present invention reach up to 240MPa, the tensile strength reach up to 420MPa, and the elongation reach up to 20%.

[0023] The content of niobium in the earth's crust is 0.002%, which is higher than Co and slightly lower than Cu and Ni. The mineral resource reserves are sufficient, and the amount of niobium-based alloy used in the die-casting aluminum alloy of the present invention is small. The niobium metal used per ton of aluminum liquid does not exceed 0.8 kg. The raw material cost is low, and recycled waste aluminum with complex composition and more impurities can be used as a raw material to manufacture high-strength and tough heat-treatment-free aluminum alloy materials, thereby reducing manufacturing costs and improving production efficiency. It can reduce costs and increase efficiency for enterprises, and promote the benign and healthy development of aluminum alloy material technology and heat-treatment-free integrated die-casting industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD pattern of Nb-35Ti-15Al-10Mo alloy used in Examples 1 to 3;

[0025] Figure 2 The XRD pattern of the die-cast aluminum alloy prepared in Example 3;

[0026] Figure 3 This is a metallographic structure image of the die-cast aluminum alloy obtained in Example 3, magnified 200 times;

[0027] Figure 4The backscattered image of the die-cast aluminum alloy obtained in Example 3 is 1000 times scanning electron microscope. (The sample was corroded by 4% nitric acid alcohol solution (volume fraction), and the metallographic sample was observed on a Leica DM IRM optical microscope (OM) and a JEOL JXA-8100 scanning electron microscope (SEM) equipped with an OXFORD7412 energy dispersive spectrometer (EDS); the phase composition analysis was performed on a D / MAX-RC X-ray diffractometer (XRD) using a Cu target; the plate tensile sample was subjected to a room temperature (293K) tensile test on a DNS200 universal material testing machine, and the tensile speed was 2 mm•min -1 . ) DETAILED DESCRIPTION

[0028] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Example 1

[0029] A renewable heat-treatment-free integrated die-casting aluminum alloy, the weight percentage of each component is Mg: 6.5%, Si: 2%, Mn: 1.5%, Zn: 0.1%, Be: 0.003%, Nb: 0.02%, Ti: 0.0175%, Mo: 0.005%, Fe: 0.15%, the total amount of other impurities is 0.35%, and the balance is Al. The die-casting aluminum alloy phase of this embodiment includes a matrix α-Al solid solution, Mg2Si and a BCC phase. The BCC phase is made of a niobium-based Nb-35Ti-15Al-10Mo alloy that is repeatedly smelted three times in a magnetic suspension melting furnace and then ball milled and sieved. Figure 1 As shown, the particle size is 2 μm and is evenly distributed in the grain boundary region of the die-cast aluminum alloy. The high melting point BCC phase has a hydrogen adsorption capacity of >150 ml / g in the temperature range of 20-700°C, and does not melt when heated to 1980°C and kept for 2 hours; the die-cast tensile strength of the die-cast aluminum alloy in this embodiment is 380 MPa, the yield strength is 210 MPa, and the elongation is 14%.

[0030] A method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy comprises the following steps:

[0031] 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 750°C, stir it evenly for 15 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0032] 2) The aluminum liquid is heated to 710°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent is sprayed at a speed of 0.6 kg / min and a nitrogen pressure of 0.35 MPa; the refining agent is prepared by mixing the components according to the corresponding percentages and loading them into a ball mill with a rotation speed of 100 r / min, mixing and grinding them into powder, and then passing through a 20-mesh sieve, and the percentages of the components constituting the refining agent are MgCl2: 42wt%, KCl: 35wt%, CaF2: 10 wt%, BaCl2: 10 wt%, and Nb-35Ti-15Al-10Mo alloy: 3wt%;

[0033] 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor speed to 400r / min, the argon pressure to 0.2MPa, the argon flow rate to 10L / min, and the degassing time to 10min; evenly sprinkle a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1:1 on the surface of the degassed aluminum liquid for slag removal. After standing for 10min, control the aluminum liquid temperature to 660℃, set a foam ceramic filter with a thickness of 8mm and an aperture of 20 mesh at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then flow through an alumina gravel deep bed filter with a particle size of 10mm for secondary filtration. After two-stage filtration, a hydrogen content of 0.05ml / 100g Al and a slag content of 0.01mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free integrated die-casting aluminum alloy has a high resistance to hydrogen embrittlement. Example 2

[0034] A renewable heat-treatment-free integrated die-casting aluminum alloy, the weight percentage of each component is Mg: 5%, Si: 2.9%, Mn: 1.25%, Zn: 0.3%, Be: 0.004%, Nb: 0.08%, Ti: 0.07%, Mo: 0.02%, Fe: 0.1%, the total amount of other impurities is 0.4%, and the balance is Al. The die-casting aluminum alloy phase of this embodiment includes a matrix α-Al solid solution, Mg2Si and a BCC phase. The BCC phase is made of a niobium-based Nb-35Ti-15Al-10Mo alloy that is repeatedly smelted three times in a magnetic suspension melting furnace and then ball-milled and sieved. Figure 1 As shown, the particle size is 1 μm and is evenly distributed in the grain boundary region of the die-cast aluminum alloy. The high melting point BCC phase has a hydrogen adsorption capacity of >150 ml / g in the temperature range of 20-700°C, and does not melt when heated to 1980°C and kept for 2 hours; the die-cast tensile strength of the die-cast aluminum alloy in this embodiment is 350 MPa, the yield strength is 180 MPa, and the elongation is 20%.

[0035] A method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy comprises the following steps:

[0036] 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 770°C, stir it evenly for 30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 710°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0037] 2) Raise the temperature of the aluminum liquid to 730°C, spray the refining agent evenly into the aluminum liquid with nitrogen load and keep it for 15 minutes. After the spraying is completed, let the aluminum liquid stand for 30 minutes to allow the refining agent particles to fully react and float up before removing the slag; the spraying speed of the refining agent is 1.0kg / min, and the nitrogen pressure is 0.8MPa; the refining agent is composed of the following components in mass fraction. The refining agent is prepared by mixing the components according to the corresponding percentage and loading them into a ball mill with a speed of 500r / min, mixing and grinding them into powder, and then passing through a 40-mesh sieve. The percentages of the components constituting the refining agent are MgCl2: 34 wt%, KCl: 50wt%, CaF2: 5wt%, BaCl2: 5wt%, Nb-35Ti-15Al-10Mo alloy: 6wt%;

[0038] 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor rotation speed to 450r / min, argon pressure to 0.35MPa, argon flow rate to 15L / min, and degassing time to 15min; evenly sprinkle a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.5 on the surface of the degassed aluminum liquid for slag removal. After standing for 20min, control the aluminum liquid temperature to 690℃, set a 20mm thick, 80 mesh foam ceramic filter at the outlet of the holding furnace aluminum liquid for primary filtration, and then flow through an alumina gravel deep bed filter with a particle size of 2mm for secondary filtration. After two-stage filtration, a hydrogen content of 0.04ml / 100g Al and a slag content of 0.005mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free integrated die-casting aluminum alloy has a high resistance to hydrogen embrittlement. Example 3

[0039] A renewable heat-treatment-free integrated die-casting aluminum alloy, the weight percentage of each component is Mg: 8.0%, Si: 3.8%, Mn: 1.0%, Zn: 0.5%, Be: 0.005%, Nb: 0.05%, Ti: 0.04375%, Mo: 0.0125%, Fe: 0.18%, the total amount of other impurities is 0.3%, and the balance is Al. The die-casting aluminum alloy phases of this embodiment include matrix α-Al solid solution, Mg2Si and BCC phases, such as Figure 2As shown in the figure, the BCC phase is obtained by repeatedly melting the niobium-based Nb-35Ti-15Al-10Mo alloy in a magnetic levitation melting furnace for three times and then ball milling and sieving. Due to the low content of the BCC phase, no corresponding diffraction peak appears in the XRD spectrum, but Figure 4 The scanning electron microscope image magnified 1000 times clearly shows that the BCC phase niobium-based alloy particles with a particle size of 1.5 μm are evenly distributed in the grain boundary area of ​​the die-cast aluminum alloy. Figure 3 It can be found from the metallographic structure image observed at 200 times magnification that the α-Al grains are significantly refined under the action of the BCC phase niobium-based alloy particle refiner, and the grain size is about 10μm. The high melting point BCC phase has a hydrogen adsorption capacity of >150ml / g in the temperature range of 20-700℃, and does not melt when heated to 1980℃ and kept for 2h; the die-cast tensile strength of the die-cast aluminum alloy in this embodiment is 420MPa, the yield strength is 240MPa, and the elongation is 8%.

[0040] A method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy comprises the following steps:

[0041] 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 760°C, stir it evenly for 25 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 700°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0042] 2) Raise the temperature of the aluminum liquid to 720°C, spray the refining agent evenly into the aluminum liquid with nitrogen load and keep it for 13 minutes. After the spraying is completed, let the aluminum liquid stand for 25 minutes to allow the refining agent particles to fully react and float up before removing the slag; the spraying speed of the refining agent is 0.8kg / min, and the nitrogen pressure is 0.6MPa; the refining agent is composed of the following components in mass fraction. The refining agent is prepared by mixing the components according to the corresponding percentage and loading them into a ball mill with a rotation speed of 300r / min, mixing and grinding them into powder, and then passing through a 30-mesh sieve. The percentage of each component constituting the refining agent is MgCl2: 55wt%, KCl: 30wt%, CaF2: 5.5wt%, BaCl2: 5.5wt%, Nb-35Ti-15Al-10Mo alloy: 4wt%;

[0043] 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 425r / min, the argon pressure is 0.3MPa, the argon flow rate is 13L / min, and the degassing time is 12min; a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.25 is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 15min, the aluminum liquid temperature is controlled at 675℃, and a foam ceramic filter with a thickness of 14mm and an aperture of 60 mesh is set at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then it flows through an alumina gravel deep bed filter with a particle size of 6mm for secondary filtration. After two-stage filtration, a hydrogen content of 0.045ml / 100g Al and a slag content of 0.008mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free integrated die-casting aluminum alloy has a high resistance to hydrogen embrittlement. Comparative Example

[0044] A secondary die-cast aluminum alloy, the weight percentage of each component is Mg: 5%, Si: 2.9%, Mn: 1.25%, Zn: 0.3%, Be: 0.004%, Fe: 0.1%, the total amount of other impurities is 0.4%, and the balance is Al. The phase of the comparative die-cast aluminum alloy includes a matrix α-Al solid solution and a Mg2Si phase; the die-cast tensile strength of the comparative die-cast aluminum alloy is 260MPa, the yield strength is 115MPa, and the elongation is 7.5%.

[0045] A method for preparing a recycled die-cast aluminum alloy comprises the following steps:

[0046] 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 770°C, stir it evenly for 30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 710°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0047] 2) The aluminum liquid is heated to 730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent is sprayed at a speed of 1.0 kg / min and a nitrogen pressure of 0.8 MPa; the refining agent is prepared by mixing the components according to corresponding percentages and loading them into a ball mill with a rotation speed of 500 r / min, and then grinding them into powder and passing through a 40-mesh sieve, and the percentages of the components constituting the refining agent are MgCl2: 50wt%, KCl: 40wt%, CaF2: 5wt%, and BaCl2: 5wt%;

[0048] 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor rotation speed to 450r / min, argon pressure to 0.35MPa, argon flow rate to 15L / min, and degassing time to 15min; evenly sprinkle a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.5 on the surface of the degassed aluminum liquid for slag removal. After standing for 20min, control the aluminum liquid temperature to 690℃, set a foam ceramic filter with a thickness of 20mm and an aperture of 80 mesh at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then flow through an alumina gravel deep bed filter with a particle size of 2mm for secondary filtration. After two-stage filtration, a hydrogen content of 0.18ml / 100g Al and a slag content of 0.012mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor to produce a die-cast aluminum alloy ingot.

[0049]

[0050] It can be seen that compared with the embodiment, since the BCC phase niobium-based Nb-35Ti-15Al-10Mo alloy is not added in the comparative refining agent, the diffusion rate of hydrogen in the aluminum liquid is reduced, and even after the refining treatment of the traditional refining agent, efficient dehydrogenation and degassing cannot be achieved, and the high hydrogen content in the aluminum liquid leads to a significant increase in the slag content, resulting in a significant decrease in the strength and toughness of the obtained die-cast aluminum alloy. The hydrogen content and slag content in the aluminum liquid are directly related, and the hydrogen reduction and slag removal measures are mutually integrated and inseparable, as shown in the performance index comparison in Table 1 above.

Claims

1. A renewable heat-treatment-free integrated die-casting aluminum alloy, characterized in that: The weight percentage of each component in the die-casting aluminum alloy is Mg: 5.0-8.0%, Si: 2.0-3.8%, Mn: 1.0-1.5%, Zn: 0.1-0.5%, Be: 0.003-0.005%, Nb: 0.02-0.08%, Ti: 0.0175-0.07%, Mo: 0.005-0.02%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al; The die-cast aluminum alloy phases include a matrix α-Al solid solution, Mg2Si and a BCC phase, wherein the BCC phase is a Nb-35Ti-15Al-10Mo niobium-based alloy, and the BCC phase is uniformly distributed in the grain boundary region of the die-cast aluminum alloy. The BCC phase has a hydrogen adsorption capacity of >150 ml / g within a temperature range of 20 to 700° C., and does not melt when heated to 1980° C. and kept warm for 2 hours; the die-cast aluminum alloy has a die-cast tensile strength of 350 to 420 MPa, a yield strength of 180 to 240 MPa, and an elongation of 8 to 20%.

2. A method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy as claimed in claim 1, characterized in that The following steps are involved: 1) Put the recycled aluminum ingot, silicon, zinc, and aluminum-manganese master alloy into a smelting furnace, heat it to 750-770°C, stir it evenly for 15-30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680-710°C, add the magnesium ingot and Al-Be master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly; 2) The aluminum liquid is heated to 710-730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10-15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20-30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent spraying speed is 0.6-1.0 kg / min, and the nitrogen pressure is 0.35-0.8 MPa; 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 400-450r / min, the argon pressure is 0.2-0.35MPa, the argon flow rate is 10-15L / min, and the degassing time is 10-15min; a layer of slag remover is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 10-20min, the aluminum liquid temperature is controlled at 660-690℃, and after two-stage filtration, an aluminum liquid with a hydrogen content of ≤0.05ml / 100g Al and a slag content of ≤0.01mm2 / kg is obtained; the aluminum liquid enters the preheated ingot mold through a distributor to obtain a heat-treatment-free die-casting aluminum alloy ingot; The refining agent in step 2) is composed of the following components in parts by weight: MgCl2 30-55 parts; KCl 30-50 parts; CaF2 5-10 parts; BaCl2 5-10 parts; 3 to 6 parts of Nb-35Ti-15Al-10Mo alloy.

3. The method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy according to claim 2, characterized in that: The slag remover in step 3) is MgCl2 and KCl in a weight ratio of 1:1 to 1.5; the two-stage filtration is to set a foam ceramic filter with a thickness of 8 to 20 mm and a pore size of 20 to 80 at the outlet of the aluminum liquid in the insulation furnace for primary filtration, and then flow through an alumina gravel deep bed filter with a particle size of 2 to 10 mm for secondary filtration.

4. The method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy according to claim 2, characterized in that: The refining agent is prepared by mixing the components according to corresponding percentages and feeding them into a ball mill with a rotation speed of 100-500 r / min, mixing and grinding them into powder, and then passing through a 20-40 mesh sieve.

5. The method for preparing a renewable heat-treatment-free integrated die-casting aluminum alloy according to claim 2, characterized in that: The Nb-35Ti-15Al-10Mo alloy is a powder particle with a particle size of 1-2 μm obtained by repeatedly smelting three times in a magnetic suspension smelting furnace and then ball milling and sieving.